A Review on Health Benefits of Malva sylvestris L. Nutritional Compounds for Metabolites, Antioxidants, and Anti-Inflammatory, Anticancer, and Antimicrobial Applications. (16th August 2021) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Behbudi, Gity; Mazraedoost, Sargol; Omidifar, Navid; Gholami, Ahmad; Chiang, Wei-Hung; Babapoor, Aziz; Pynadathu Rumjit, Nelson
Abstract : The utilization of medicinal plants and their derivatives in treating illnesses is more appropriately recognized as herbal remedy than traditional medicine. For centuries, medicinal herbs have been used for the treatment of diseases in many countries. Malva sylvestris L. is a kind of mallow derived from Malvaceae species and is recognized as common mallow. This amazing plant has antimicrobial, hepatoprotective, anti-inflammatory, and antioxidant properties and is considered as one of the most promising herbal medicinal species. This plant's traditional use in treating many diseases and preparing pharmaceutical compounds can show us how to know in depth the plant origin of drugs used to produce antibiotics and other therapeutic agents.